Kepuasan Pengguna dan Manfaat Coretax dalam Administrasi Perpajakan Digital - Rezky Akbar Setyanto Putra; Tresno Eka Jaya; Aji Ahmadi Sasmi (LPPM Universitas Negeri Jakarta, 2026)
The purpose of this study is to assess the Coretax Administration System's deployment success using the DeLone and McLean Information System Success Model. The study looks at how user happiness affects net benefits as well as how system, information, and service quality affect user satisfaction. Data gathered from surveys given to Coretax customers was used in a quantitative manner. The Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach was used to examine the data. The findings show that user satisfaction is positively and significantly impacted by system, information, and service quality. Additionally, net benefits are positively and significantly impacted by customer happiness. These results imply that enhancing system, information, and service quality can increase user satisfaction and optimize the advantages of implementing a digital tax system.